Is Quality of Higher Educational Institutions in Western Balkan Real? - Živaljević, Aleksandra; Vrcelj, Nikolina; Tošović-Stevanović, Aleksandra (Industrija, 2015)
The paper presents a survey conducted in November of 2013 in 120 higher education institutions in the Western Balkans Countries, with purpose to determine which models are used for quality improvement in Western Balkans higher educational institutions, and whether critical conditions for continuous quality improvement have been met by applying those models. Data were obtained by using questionnaire which consisted of 24 questions related to 2 previously defined hypotheses. Gathered data were tested with Student's t test to determine if there is a significant difference between the groups of higher educational institutions which use different quality models, as well as between private and public higher educational institutions. Authors argue that the rules imposed by Governments do not provide sufficient incentive for meeting the critical conditions for the continuous quality improvement. Legal framework and mandatory accreditation conducted by government bodies lead higher educational institutions to fulfil the formal requirements, distancing them from the essence of quality management, i.e. from self-criticism and motivation to consistently deliver better results than the previous ones and giving them the illusion of achieving quality through compliance with formal criteria.
Keywords: Process; Higher education institution; Quality management; Standardization; Knowledge management